Diseminasi Proses Sertifikasi Halal pada Perajin Kemplang Desa Meranjat Ilir Kecamatan Indralaya Selatan: Dissemination of Halal Certification Process to Kemplang Crafters in Meranjat Ilir Village, South Indralaya District - Syafutri, Merynda Indriyani; Syaiful, Friska; Lidiasari, Eka; Widowati, Tri Wardani; Sugito, Sugito; Pratama, Filli; Parwiyanti, Parwiyanti; Yanuriati, Anny (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Meranjat Ilir Village is located in the South Indralaya District, Ogan Ilir Regency, South Sumatra Province, with one of the leading products, kemplang. The kemplang business is the main livelihood for the community, as well as an income for craftswomen in Meranjat Ilir Village. One important factor in maintaining product quality, increasing selling value in marketing, and business sustainability is halal certification. The awareness of small and medium entrepreneurs to carry out halal certification is very low. Therefore, an activity is needed to socialize the halal certification process. This community service activity aimed to provide knowledge and understanding, as well as socialize with the community of kemplang crafters in Meranjat Ilir Village regarding the halal certification process for food products, especially kemplang products. The method used was the lecturing method which was carried out through the presentation and explanation of material accompanied by discussion and question-answer. The target audience in this activity was the community of kemplang crafters in Meranjat Ilir Village. The results showed that kemplang crafters in Meranjat Ilir Village gained knowledge and understanding of the halal certification process. There was an increase in understanding of the target audience by 28.39% after the presentation of the material.